A positive electrode active material, a preparation method thereof and an electric device
By forming a three-layer cladding layer containing lithium transition metal salt or oxide on the substrate surface of the nickel-cobalt manganese oxide positive electrode active material, the problem of insufficient power performance of existing materials at low SOC is solved, and a higher battery is achieved Cycling performance and stability.
Patent Information
- Application Number
- CN202210043224.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-01-14
AI Technical Summary
The existing ternary positive electrode active materials, especially nickel-cobalt lithium manganate, have a high operating voltage platform range, resulting in insufficient power performance under low charge state.
A lithium-containing transition metal salt or lithium-containing transition metal oxide is used as the cladding layer, and a three-layer structure cladding layer is formed on the surface of the substrate of the nickel-cobalt-manganate lithium material, and multiple working voltage platforms with gradients are provided.
The power performance of the battery cell in a low SOC state is improved, and the cycle performance of the battery and the stability of the positive electrode active material are improved.
Smart Images

Figure CN115832233B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of electrochemistry, and in particular to a positive electrode active material, a preparation method thereof, a secondary battery, a battery module, a battery pack and an electrical device. Background Art
[0002] Faced with increasingly tight energy resources, new energy storage devices have made significant progress. Among them, lithium-ion batteries have attracted much attention due to their high energy density, high capacity, good cycle stability and environmental protection characteristics. In lithium-ion batteries, ternary positive electrode active materials have become the darling of positive electrode active materials because they have higher specific capacity and lower cost than single positive electrode active materials. Compared with lithium manganese oxide, lithium nickel cobalt manganese oxide has greatly improved high-temperature cycle stability; compared with lithium iron phosphate, lithium nickel cobalt manganese oxide has higher energy density and good batch stability in production. Therefore, lithium nickel cobalt manganese oxide is considered to be the preferred ternary positive electrode active material for future large-scale power batteries. At present, high energy density, high power, and long cycle ternary positive electrode active materials have become one of the research and development focuses in the field of lithium-ion batteries. Summary of the invention
[0003] The operating voltage platform range of existing ternary positive electrode active materials, especially nickel cobalt manganese oxide lithium ternary positive electrode active materials, is relatively high. Excessively high discharge platforms will limit the power performance of battery cells at low states of charge (SOC). In order to improve the power performance of battery cells at low SOC states, the present disclosure provides a positive electrode active material, a preparation method thereof, and a secondary battery, battery module, battery pack and power-consuming device containing the positive electrode active material, which can improve the shortcomings of poor power performance of existing ternary positive electrode active materials at low SOC states, and can also improve the cycle performance of battery cells and improve the stability of positive electrode active materials.
[0004] In a first aspect, the present disclosure provides a positive electrode active material, the positive electrode active material comprising a substrate and a coating layer, the substrate comprising Li 1+a Ni x Co y Mn z M b N c O2, wherein M and N are respectively one of Al, Fe, Zn, V, Cr, Nb, Ca and Mg, and the values of a, b, c, x, y and z satisfy the following conditions at the same time: 0<a<0.2, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤b≤1, 0≤c≤1, and x+y+z+b+c=1; the coating layer has a three-layer structure, which includes a first coating layer, a second coating layer and a third coating layer in sequence from the surface of the substrate to the outside, and the first coating layer is Li 1+x1 V3O8, the second coating layer is Li 1.2 Tix2 Ni y2 O2, the third coating layer is LiMn x3 Fe y3 PO4, where 0≤x1≤0.2, 0≤x2≤0.8, 0≤y2≤0.8, x2+y2=0.8, 0≤x3≤1, 0≤y3≤1, x3+y3=1.
[0005] In some embodiments of the present disclosure, the first coating layer is LiV3O8, and the second coating layer is Li 1.2 Ti 0.6 Ni 0.2 O2, the third coating layer is LiMn 0.75 Fe 0.25 At least one of PO4 or LiFePO4.
[0006] In the technical solution of the embodiment of the present disclosure, the coating layer is a lithium-containing transition metal salt or a lithium-containing transition metal oxide. Through different coating layers, multiple operating voltage platforms with gradients can be set to make up for the disadvantage that the nickel-cobalt-manganese-lithium ternary positive electrode active material lacks an operating voltage platform in a low voltage range, thereby improving the power performance of the battery cell in a low SOC state. In addition, the coating layer containing a lithium transition metal salt or a lithium transition metal oxide has a high lithium ion conductivity and good structural stability, which can inhibit the structural changes and composition changes of the nickel-cobalt-manganese-lithium matrix under high voltage, thereby improving the cycle performance and stability of the battery cell.
[0007] In the technical solution of the embodiment of the present disclosure, the outermost layer of the coating layer is a lithium iron phosphate material. Such materials have advantages such as good stability. Placing materials with good stability on the outer layer of the coating layer can improve the stability of the positive electrode active material and reduce the increase of current impedance under long cycles.
[0008] In some embodiments of the present disclosure, the thickness of the first coating layer is 20-100 nm, and optionally, 30-70 nm.
[0009] In some embodiments of the present disclosure, the thickness of the second coating layer is 20-100 nm, and optionally, 30-70 nm.
[0010] In some embodiments of the present disclosure, the thickness of the third coating layer is 20-100 nm, and optionally, 30-70 nm.
[0011] In the technical solution of the embodiment of the present disclosure, the coating layer material has a high ionic conductivity and a low electronic conductivity. When the coating layer is too thick, the resistance of the material increases and the electrochemical activity decreases; and when the coating layer is too thin, the coating effect cannot be achieved. By setting the thickness of each coating layer within the range of 20-100nm, the gram capacity of the positive electrode active material will not be affected.
[0012] In a second aspect, the present disclosure provides a method for preparing the positive electrode active material, the method comprising at least the following steps:
[0013] Step (1): adding the matrix, lithium source and vanadium source into an aqueous solution in a molar ratio, adding a citric acid solution and drying, and then sintering to obtain material A;
[0014] Step (2): adding the material A to an aqueous solution containing a lithium source, a nickel source and a titanium source for hydrothermal reaction, filtering after the hydrothermal reaction, and sintering the obtained solid to obtain material B;
[0015] Step (3): adding the material B to an aqueous solution containing a lithium source, an iron source and a phosphorus source, adjusting the pH of the solution and adding a surfactant to carry out a hydrothermal reaction, filtering after the hydrothermal reaction is completed, and sintering the obtained solid to obtain the positive electrode active material.
[0016] In the technical solution of the embodiment of the present disclosure, the present disclosure forms the coating layer by in-situ growth on the surface of the substrate, so the coating layer can be uniformly formed on the surface of the substrate; in addition, compared with the non-in-situ coating method, the coating amount of the coating layer in the positive electrode active material of the present disclosure is easier to accurately control; at the same time, the synthesis method of the present disclosure can meet the customer's needs for different working voltage platforms of the positive electrode active material, and the elements used in the synthetic material are all cheap metals with low cost.
[0017] In some embodiments of the present disclosure, in the step (1), the sintering temperature is 300-800° C., and the sintering time is 12-24 hours.
[0018] In some embodiments of the present disclosure, in the step (2), the hydrothermal reaction temperature is 150-250° C., and the hydrothermal reaction time is 12-48 h.
[0019] In some embodiments of the present disclosure, in step (3), the hydrothermal reaction temperature is 100-200° C., and the hydrothermal reaction time is 6-24 h.
[0020] In the technical solution of the embodiment of the present disclosure, too high a reaction temperature will lead to excessive volatilization of the lithium source. Appropriate reaction temperature and time are conducive to the synthesis of a coating layer with a target stoichiometric ratio and a suitable thickness.
[0021] In a third aspect, the present disclosure provides a secondary battery, the secondary battery comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode active material of the present disclosure.
[0022] In a fourth aspect, the present disclosure provides a battery module, wherein the battery module includes the secondary battery according to the third aspect of the present disclosure.
[0023] In a fifth aspect, the present disclosure provides a battery pack, comprising the battery module of the fourth aspect of the present disclosure.
[0024] In a sixth aspect, the present disclosure provides an electrical device, comprising at least one selected from the secondary battery of the third aspect of the present disclosure, the battery module of the fourth aspect of the present disclosure, or the battery pack of the fifth aspect of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present disclosure.
[0026] Figure 2 yes Figure 1 FIG. 2 is an exploded view of a secondary battery according to an embodiment of the present disclosure.
[0027] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present disclosure.
[0028] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present disclosure.
[0029] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present disclosure is shown.
[0030] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present disclosure as a power source.
[0031] Description of reference numerals:
[0032] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0033] The following is a detailed description of the embodiments of the technical solution of the present disclosure. The following embodiments are only used to more clearly illustrate the technical solution of the present disclosure, and are therefore only used as examples, and cannot be used to limit the protection scope of the present disclosure.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field of the present disclosure; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure; the terms "including" and "having" in the specification and claims of the present disclosure and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions; the terms "plurality" and "multiple" mean two, more than two, including two or two, unless otherwise clearly and specifically defined.
[0035] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present disclosure. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0036] In the description of the embodiments of the present disclosure, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0037] Lithium-ion batteries dominate the global secondary battery market due to their high operating voltage, wide operating range, high specific energy, no pollution, and long service life. In particular, they have been widely used in electric vehicles and other fields in recent years. The positive electrode active material of lithium-ion batteries is one of the important components of lithium-ion batteries and plays a vital role in the electrochemical performance of lithium-ion batteries. At present, with the continuous improvement of the demand for battery performance, ternary positive electrode active materials, especially nickel cobalt manganese oxide ternary positive electrode active materials, have better electrochemical properties than other commonly used lithium-ion battery positive electrode active materials such as lithium manganese oxide, lithium iron phosphate and lithium cobalt oxide, and have become popular battery positive electrode active materials.
[0038] At present, the market demand for battery cells with low operating voltage platforms is increasing, requiring battery cells to still have good power performance at low SOC. However, the existing ternary positive electrode active materials, especially the nickel cobalt manganese oxide lithium ternary positive electrode active materials, have a high operating voltage platform range. Too high a discharge platform will limit the power performance of battery cells at low SOC, so the existing ternary positive electrode active materials can no longer meet people's requirements for battery cells to have high power performance at low SOC.
[0039] In order to solve the above problems, the inventors of the present disclosure have found that a lithium-containing transition metal salt or a lithium-containing transition metal oxide can be coated on the surface of the nickel-cobalt-manganese-oxide lithium material matrix to form a mixed positive electrode active material with a coating layer. Since different coating layers can have different operating voltage platform ranges, the positive electrode active material can still have an operating voltage platform in a low voltage range, so the power performance of the battery cell at a low SOC state can be improved, thereby meeting people's requirements for high power performance of the battery cell at a low SOC.
[0040] The positive electrode active material disclosed in the embodiments of the present disclosure, and the secondary battery, battery module and battery pack comprising the positive electrode active material of the present disclosure can be used in, but not limited to, electrical devices such as vehicles, ships or aircraft.
[0041] Positive electrode active material
[0042] According to an embodiment of the present disclosure, the present disclosure provides a positive electrode active material, the positive electrode active material includes a substrate and a coating layer, the substrate includes Li 1+a Ni x Co y Mn z M b N c O2, wherein M and N are one of Al, Fe, Zn, V, Cr, Nb, Ca and Mg respectively, and the values of a, b, c, x, y and z satisfy the following conditions at the same time: 0<a<0.2, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤b≤1, 0≤c≤1, and x+y+z+b+c=1; the coating layer has a three-layer structure, including a first coating layer, a second coating layer and a third coating layer in sequence from the substrate surface to the outside, and the first coating layer is Li 1+x1 V3O8, the second coating layer is Li 1.2 Ti x2 Ni y2 O2, the third coating layer is LiMn x3 Fe y3 PO4, where 0≤x1≤0.2, 0≤x2≤0.8, 0≤y2≤0.8, x2+y2=0.8, 0≤x3≤1, 0≤y3≤1, x3+y3=1.
[0043] In some embodiments of the present disclosure, the first coating layer includes but is not limited to LiV3O8, Li 1.1 V3O8 and Li 1.2 One or more of V3O8, the second coating layer includes but is not limited to Li 1.2 Ti 0.2 Ni 0.6 O2、Li 1.2 Ti 0.4 Ni 0.4O2、Li 1.2 Ti 0.6 Ni 0.2 O2、Li 1.2 Ti 0.8 O2 and Li 1.2 Ni 0.8 O2, the third coating layer includes but is not limited to LiMn 0.75 Fe 0.25 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn 0.25 Fe 0.75 One or more of PO4 and LiFePO4. The coating layer can be selected according to the requirements of different working voltage platforms of the positive electrode active material.
[0044] In some embodiments of the present disclosure, the matrix is Li 1+a Ni x Co y Mn z O2, wherein 0<a<0.2, 0≤x≤1, 0≤y≤1, 0≤z≤1, and x+y+z=1.
[0045] In some embodiments of the present disclosure, the matrix may specifically include Li 1+a Ni 0.8 Co 0.1 Mn 0.1 O2、Li 1+ a Ni 0.6 Co 0.2 Mn 0.2 O2、Li 1+a Ni 0.5 Co 0.3 Mn 0.2 O2、Li 1+a Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and Li 1+a Ni 0.8 Co 0.15 Mn 0.05 O2 one or more of the nickel-cobalt-manganese-oxide lithium ternary positive electrode active materials.
[0046] In some embodiments of the present disclosure, the matrix may specifically include LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.5 Co0.3 Mn 0.2 O2、LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 and LiNi 0.8 Co 0.15 Mn 0.05 O2 one or more of the nickel-cobalt-manganese-oxide lithium ternary positive electrode active materials.
[0047] In some embodiments of the present disclosure, the substrate is LiNi 0.8 Co 0.1 Mn 0.1 O2.
[0048] The coating layer using lithium-containing transition metal salt or lithium-containing transition metal oxide as the matrix has many advantages:
[0049] (1) Multiple operating voltage platforms with gradients can be set through different coating layers. The different operating voltage platform ranges of the coating layers expand the operating range of the positive electrode active material and make up for the shortcomings of positive electrode active materials such as nickel cobalt manganese oxide that lack an operating voltage platform in the low voltage range. The low power at low SOC is often due to the limitation of the battery's own discharge platform. Having an operating voltage platform in the low voltage range can improve the power performance of the battery cell at low SOC.
[0050] (2) The coating layer containing lithium transition metal salt or lithium transition metal oxide has high lithium ion conductivity and good structural stability, which can inhibit the structural and composition changes of the lithium nickel cobalt manganese oxide matrix under high voltage, thereby improving the cycle performance and stability of the battery cell.
[0051] (3) Lithium-containing transition metal salts or lithium-containing transition metal oxides have a larger lattice spacing, better ion conductivity and better corrosion resistance, and exhibit the characteristics of low impedance, good rate performance, wide voltage window and good stability.
[0052] (4) The coating layer can reduce the direct contact area between the positive electrode active material matrix and the electrolyte, reduce the corrosion of HF in the electrolyte to the material, inhibit the occurrence of side reactions, and improve the structural stability of the positive electrode active material.
[0053] In addition, nickel cobalt lithium manganese oxide materials are used in the positive electrode active material matrix. This type of material has excellent electrochemical properties such as high capacity, good thermal stability, wide charge and discharge voltage, and good cycle performance, and is an important component of the positive electrode active material. Metal elements such as Al, Fe, Zn, V, Cr, Nb, Ca or Mg are doped in the positive electrode active material. Since the ionic radius of the doped elements is slightly smaller than that of Ni, Co and Mn elements, the doped elements can be better embedded in the body center position of the matrix structure to stabilize the structure of the material. At the same time, nickel and manganese are relatively cheap transition metals, which can reduce the cost of positive electrode active materials. In the technical solution of the embodiment of the present disclosure, LiNi is used. 0.8 Co 0.1 Mn 0.1 O2 as the matrix. 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.5 Co 0.3 Mn 0.2 O2 and other commonly used nickel cobalt manganese oxide ternary positive electrode active materials, LiNi 0.8 Co 0.1 Mn 0.1 O2 has a higher energy density.
[0054] In some embodiments of the present disclosure, the first coating layer is LiV3O8 and the second coating layer is Li 1.2 Ti 0.6 Ni 0.2 O2, the third coating layer is LiMn 0.75 Fe 0.25 At least one of PO4 or LiFePO4.
[0055] In some embodiments of the present disclosure, the first coating layer is LiV3O8 and the second coating layer is Li 1.2 Ti 0.6 Ni 0.2 O2, and the third coating layer is LiFePO4.
[0056] The substrate is coated with three layers of coating layers, and different coating layers have different working voltage platforms. The working voltage platform of LiV3O8 is 2.5-2.8V, and the working voltage platform of Li 1.2 Ti 0.6 Ni 0.2 The operating voltage platform of O2 is 2.9-3.2V, and that of LiMn 0.75 Fe 0.25The working voltage platform of PO4 is 3.3-3.6V, and the working voltage platform of LiFePO4 is 3.2-3.4V, so that the positive electrode active material still has a working voltage platform at a lower voltage range, thereby improving the power performance of the positive electrode active material under low SOC. At the same time, placing the lithium-containing transition metal phosphate with good stability in the outer layer can improve the stability of the positive electrode active material.
[0057] In some embodiments of the present disclosure, the thickness of the first cladding layer is 20-100 nm, optionally, 30-70 nm, and further optionally, 40 nm.
[0058] In some embodiments of the present disclosure, the thickness of the second cladding layer is 20-100 nm, optionally, 30-70 nm, and further optionally, 40 nm.
[0059] In some embodiments of the present disclosure, the thickness of the third cladding layer is 20-100 nm, optionally, 30-70 nm, and further optionally, 40 nm.
[0060] In some embodiments of the present disclosure, the thickness of the first cladding layer is 20-100 nm, the thickness of the second cladding layer is 20-100 nm, and the thickness of the third cladding layer is 20-100 nm.
[0061] In some embodiments of the present disclosure, the thickness of the first cladding layer is 30-70 nm, the thickness of the second cladding layer is 30-70 nm, and the thickness of the third cladding layer is 30-70 nm.
[0062] In some embodiments of the present disclosure, the thickness of the first cladding layer is 40 nm, the thickness of the second cladding layer is 40 nm, and the thickness of the third cladding layer is 40 nm.
[0063] When the coating layer is too thick, the resistance of the material increases and the electrochemical activity decreases; and when the coating layer is too thin, the coating effect cannot be achieved. The coating layer material disclosed in the present invention has a high ion conductivity and a low electronic conductivity. When the thickness of each coating layer is set in the range of 20-100nm, the coating effect is achieved without affecting the gram capacity of the positive electrode active material. When the coating layer thickness is 40nm, the coating effect is better.
[0064] Method for preparing positive electrode active material
[0065] According to one embodiment of the present disclosure, the present disclosure provides a method for preparing a positive electrode active material, comprising at least the following steps:
[0066] Step (1): adding the matrix, lithium source and vanadium source into an aqueous solution in a molar ratio, adding a citric acid solution and drying, and then sintering to obtain material A;
[0067] Step (2): adding the material A to an aqueous solution containing a lithium source, a nickel source and a titanium source for hydrothermal reaction, filtering after the hydrothermal reaction, and sintering the obtained solid to obtain material B;
[0068] Step (3): adding the material B to an aqueous solution containing a lithium source, an iron source and a phosphorus source, adjusting the pH of the solution and adding a surfactant to carry out a hydrothermal reaction, filtering after the hydrothermal reaction is completed, and sintering the obtained solid to obtain the positive electrode active material.
[0069] In the technical solution of the embodiment of the present disclosure, the present disclosure forms the coating layer by in-situ growth on the surface of the substrate, so the coating layer can be uniformly formed on the surface of the substrate; in addition, compared with the non-in-situ coating method, the coating amount of the coating layer in the positive electrode active material of the present disclosure is easier to accurately control; at the same time, the synthesis method of the present disclosure can meet the customer's needs for different working voltage platforms of the positive electrode active material, and the elements used in the synthetic material are all cheap metals with low cost.
[0070] In some embodiments of the present disclosure, the lithium source is one or more of lithium carbonate, lithium oxalate, lithium acetate, lithium hydroxide, lithium nitrate and lithium sulfate, preferably LiOH·H2O.
[0071] In some embodiments of the present disclosure, in step (1), the vanadium source is one or more of vanadium pentoxide, ammonium metavanadate, ammonium vanadate, vanadium trioxide and vanadyl oxalate, preferably ammonium vanadate.
[0072] In some embodiments of the present disclosure, in step (1), the molar ratio of lithium element to vanadium element may be 1:3, 1.1:3 or 1.2:3, preferably, 1.2:3.
[0073] In some embodiments of the present disclosure, in step (1), the substrate, the lithium source and the vanadium source are added to the aqueous solution to form a uniform system.
[0074] In some embodiments of the present disclosure, in step (1), the substrate, the lithium source and the vanadium source are added to the aqueous solution and stirred to form a uniform system.
[0075] In some embodiments of the present disclosure, in step (1), the homogeneous system is sonicated, and a citric acid solution is slowly added thereto.
[0076] In some embodiments of the present disclosure, in step (1), the citric acid solution is a saturated solution.
[0077] In some embodiments of the present disclosure, in step (1), the sintering temperature is 300-800° C., and the sintering time is 12-24 hours.
[0078] In some embodiments of the present disclosure, in step (1), the sintering temperature is 400-600° C., and the sintering time is 15-22 hours.
[0079] In some embodiments of the present disclosure, in step (1), the sintering temperature is 500° C. and the sintering time is 20 h.
[0080] The calcination of the substrate and the first coating layer raw materials requires an appropriate temperature range and time. When the temperature is too high, the lithium source will volatilize too much. When the temperature is too low, the coating layer cannot form a corresponding lattice structure, resulting in poor chemical activity. Under the condition of calcination temperature of 300-800℃ and calcination for 12-24h, the first coating layer with the target stoichiometric ratio and target thickness can be obtained.
[0081] In some embodiments of the present disclosure, in step (2), the nickel source is one or more of nickel carbonate, nickel nitrate, nickel chloride, nickel oxalate and nickel sulfate, preferably nickel chloride; the titanium source is one or more of titanium carbonate, titanium nitrate, titanium chloride, titanium oxalate and titanium sulfate, preferably titanium chloride.
[0082] In some embodiments of the present disclosure, in step (2), there is no special requirement for the molar ratio of titanium element to nickel element, and it can be 1:1, 2:1 or 3:1, etc., preferably, it is 3:1.
[0083] In some embodiments of the present disclosure, in step (2), the hydrothermal reaction temperature is 150-250° C., and the hydrothermal reaction time is 12-48 h.
[0084] In some embodiments of the present disclosure, in step (2), the hydrothermal reaction temperature is 180-220° C., and the hydrothermal reaction time is 20-40 h.
[0085] In some embodiments of the present disclosure, in step (2), the hydrothermal reaction temperature is 200° C. and the hydrothermal reaction time is 24 h.
[0086] In some embodiments of the present disclosure, in step (2), the sintering temperature is 250-350° C., and the sintering time is 3-8 h.
[0087] In some embodiments of the present disclosure, in step (2), the sintering temperature is 300° C. and the sintering time is 5 h.
[0088] The calcination of the raw materials of the first coating layer and the second coating layer requires an appropriate temperature range and time. When the temperature is too high, the lithium source will volatilize too much. When the temperature is too low, the coating layer cannot form a corresponding lattice structure, resulting in poor chemical activity. Under the condition of a hydrothermal reaction temperature of 150-250°C and a reaction time of 12-48h, a second coating layer with a target stoichiometric ratio and a target thickness can be obtained.
[0089] In some embodiments of the present disclosure, in step (3), the iron source is one or more of ferric nitrate, ferric chloride, ferric phosphate, ferric sulfate and ferrous sulfate, preferably FeSO4·7H2O; the phosphorus source is one or more of diammonium hydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, phosphoric acid and pyrophosphoric acid, preferably phosphoric acid.
[0090] In some embodiments of the present disclosure, in step (3), the molar ratio of lithium element, iron element and phosphorus element can be 3:1:1.
[0091] In some embodiments of the present disclosure, in step (3), the pH adjuster includes one or more of sodium dihydrogen phosphate, disodium hydrogen phosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, boric acid, borax, acetic acid, sodium acetate, citric acid, sodium citrate, tartaric acid, sodium tartrate, sodium carbonate, ammonia water, potassium carbonate, sodium bicarbonate, potassium bicarbonate, sodium hydroxide, potassium hydroxide, hydrochloric acid and phosphoric acid. Preferably, the pH adjuster is sodium carbonate.
[0092] In some embodiments of the present disclosure, in step (3), the pH value ranges from 7 to 10, preferably, the pH value is 8.5.
[0093] In some embodiments of the present disclosure, in step (3), the surfactant includes one or more of poloxamer, sodium dodecyl sulfate, Tween-20, Tween-40, Tween-60, Tween-65, Tween-80, Tween-85, lecithin, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycols and polyethylene glycol 15-hydroxystearate, preferably, the surfactant is polyvinyl alcohol.
[0094] In some embodiments of the present disclosure, in step (3), the hydrothermal reaction temperature is 100-200° C., and the hydrothermal reaction time is 6-24 h.
[0095] In some embodiments of the present disclosure, in step (3), the hydrothermal reaction temperature is 120-180° C., and the hydrothermal reaction time is 8-12 h.
[0096] In some embodiments of the present disclosure, in step (3), the hydrothermal reaction temperature is 150° C. and the hydrothermal reaction time is 10 h.
[0097] In some embodiments of the present disclosure, in step (3), the sintering temperature is 220-300° C., and the sintering time is 2-5 h.
[0098] In some embodiments of the present disclosure, in step (3), the sintering temperature is 250° C. and the sintering time is 3 h.
[0099] The calcination of the raw materials for the second coating layer and the third coating layer requires an appropriate temperature range and time. When the temperature is too high, the lithium source will volatilize too much. When the temperature is too low, the coating layer cannot form a corresponding lattice structure, resulting in poor chemical activity. Under the condition of a hydrothermal reaction temperature of 100-200°C and a reaction time of 6-24h, a third coating layer with a target stoichiometric ratio and target thickness can be obtained.
[0100] According to one embodiment of the present disclosure, the present disclosure provides a secondary battery, which includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet includes the positive active material of the present disclosure.
[0101] According to one embodiment of the present disclosure, the present disclosure provides a battery module including the secondary battery of the present disclosure.
[0102] According to one embodiment of the present disclosure, the present disclosure provides a battery pack, which includes the battery module of the present disclosure.
[0103] According to one embodiment of the present disclosure, the present disclosure provides an electric device, which includes at least one selected from the secondary battery of the present disclosure, the battery module of the present disclosure, or the battery pack of the present disclosure.
[0104] The secondary battery, battery module, battery pack and electric device disclosed in the present invention are described below with reference to the accompanying drawings.
[0105] In some embodiments of the present disclosure, a secondary battery may be provided. Generally, the secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0106] [Positive electrode]
[0107] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material disclosed in the present invention.
[0108] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0109] In some embodiments of the present disclosure, the positive electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0110] In some embodiments of the present disclosure, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0111] In some embodiments of the present disclosure, the positive electrode film layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0112] In some embodiments of the present disclosure, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0113] [Negative electrode]
[0114] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.
[0115] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0116] In some embodiments of the present disclosure, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0117] In some embodiments of the present disclosure, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present disclosure is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0118] In some embodiments of the present disclosure, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0119] In some embodiments of the present disclosure, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0120] In some embodiments of the present disclosure, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0121] In some embodiments of the present disclosure, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0122] [Electrolytes]
[0123] The electrolyte plays a role in conducting ions between the positive electrode and the negative electrode. The present disclosure has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0124] In some embodiments of the present disclosure, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0125] In some embodiments of the present disclosure, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0126] In some embodiments of the present disclosure, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0127] In some embodiments of the present disclosure, the electrolyte may further optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0128] [Isolation film]
[0129] In some embodiments of the present disclosure, the secondary battery further includes a separator. The present disclosure has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0130] In some embodiments of the present disclosure, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0131] In some embodiments of the present disclosure, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0132] In some embodiments of the present disclosure, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0133] In some embodiments of the present disclosure, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0134] The present disclosure has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0135] In some embodiments of the present disclosure, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0136] In some embodiments of the present disclosure, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0137] Figure 3 This is a battery module 4 as an example. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0138] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0139] In some embodiments of the present disclosure, the battery modules mentioned above may also be assembled into a battery pack. The number of battery modules contained in the battery pack may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0140] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0141] In addition, the present disclosure further provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided by the present disclosure. The secondary battery, battery module, or battery pack disclosed in the present disclosure can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device disclosed in the present disclosure may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0142] As the electric device of the present disclosure, a secondary battery, a battery module or a battery pack can be selected according to its use requirements.
[0143] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0144] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0145] Example
[0146] Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available conventional products. Unless otherwise specified, the experiments were performed under conventional conditions or conditions recommended by the manufacturer.
[0147] Example 1
[0148] (1) Purchase 0.1 mol LiNi 0.8 Co 0.1 Mn 0.1O2 (Guangzhou Bangpu Technology) was ground and added to a beaker. 0.007 mol LiOH·H2O and 0.021 mol NH4VO3 were mixed and added to the beaker and dissolved in a certain amount of deionized water. A saturated citric acid solution was prepared, in which the molar mass of citric acid was equal to the total number of moles of metal ions. At 80°C
[0149] Under the conditions, the mixed salt solution is stirred with a magnetic stirrer to be evenly dispersed in the water. When the solution forms a uniform system, it is ultrasonically treated, and a saturated citric acid solution is slowly added dropwise to the solution. The color of the solution gradually changes from light yellow to reddish brown, then to dark green, and finally to dark blue. Keep the temperature unchanged and continue ultrasonic treatment for 1 hour to allow the reaction to proceed fully. After the reaction is completed, the water is evaporated to obtain a dark blue wet gel. The wet gel is dried in a drying oven at 100°C for 2 hours to obtain a loosely porous dark blue LiV3O8 precursor material. The material coated with the LiV3O8 precursor is placed in a muffle furnace and calcined at 500°C for 20 hours to obtain material A.
[0150] (2) 0.1 mol of material A was added to an aqueous solution containing 2 mol of LiOH, 0.0075 mol of TiCl4 and 0.0025 mol of NiCl2, and the mixed solution was reacted in a hydrothermal reactor at 200°C for 24 hours. After the hydrothermal reaction was completed, the mixture was filtered and the obtained solid was sintered at 300°C for 5 hours to obtain material B.
[0151] (3) Add 0.1 mol of material B to an aqueous solution containing 0.003 mol of FeSO4·7H2O, 0.003 mol of H3PO4 and 0.009 mol of LiOH·H2O, and adjust the pH value of the mixed solution with sodium carbonate. When the pH value of the mixed solution is 8.5, add the surfactant polyvinyl alcohol. Transfer the solution to a hydrothermal reactor, and set the reaction temperature to 150°C and the reaction time to 10 h. After the hydrothermal reaction is completed, filter the solution, and sinter the obtained solid at 250°C for 3 h to obtain the positive electrode active material.
[0152] Example 2
[0153] (1) Purchase 0.1 mol LiNi 0.8 Co 0.1 Mn 0.1O2 (Guangzhou Bangpu Technology) was ground and added to a beaker. 0.0093 mol LiOH·H2O and 0.028 mol NH4VO3 were mixed and added to the beaker together and dissolved in a certain amount of deionized water. A saturated citric acid solution was prepared, in which the molar mass of citric acid was equal to the total number of moles of metal ions. The mixed salt solution was stirred with a magnetic stirrer at 80°C to make it uniformly dispersed in water. When the solution formed a uniform system, it was ultrasonically treated and the saturated citric acid solution was slowly added dropwise to the solution. The color of the solution gradually changed from light yellow to reddish brown, then to dark green, and finally to dark blue. Keeping the temperature constant, the ultrasonic treatment was continued for 1 hour to allow the reaction to proceed fully. After the reaction was completed, the water was evaporated to obtain a dark blue wet gel. The wet gel was dried in a drying oven at 100°C for 2 hours to obtain a loose and porous dark blue LiV3O8 precursor material. The material coated with the LiV3O8 precursor was placed in a muffle furnace and calcined at 500°C for 20 hours to obtain material A.
[0154] (2) 0.1 mol of material A was added to an aqueous solution containing 2 mol of LiOH, 0.01 mol of TiCl4 and 0.003 mol of NiCl2, and the mixed solution was reacted in a hydrothermal reactor at 200°C for 24 h. After the hydrothermal reaction was completed, the mixture was filtered and the obtained solid was sintered at 300°C for 5 h to obtain material B.
[0155] (3) Add 0.1 mol of material B to an aqueous solution containing 0.004 mol of FeSO4·7H2O, 0.004 mol of H3PO4 and 0.012 mol of LiOH·H2O, adjust the pH value of the mixed solution with sodium carbonate, and add a surfactant, polyvinyl alcohol, when the pH value of the mixed solution is 8.5. Transfer the solution to a hydrothermal reactor, and set the reaction temperature to 150°C and the reaction time to 10 h. After the hydrothermal reaction is completed, filter the solution, and sinter the obtained solid at 250°C for 3 h to obtain a positive electrode active material.
[0156] Example 3
[0157] (1) Purchase 0.1 mol LiNi 0.8 Co 0.1 Mn 0.1O2 (Guangzhou Bangpu Technology) was ground and added to a beaker. 0.0116 mol LiOH·H2O and 0.034 mol NH4VO3 were mixed and added to the beaker together and dissolved in a certain amount of deionized water. A saturated citric acid solution was prepared, in which the molar mass of citric acid was equal to the total number of moles of metal ions. The mixed salt solution was stirred with a magnetic stirrer at 80°C to make it uniformly dispersed in water. When the solution formed a uniform system, it was ultrasonically treated and the saturated citric acid solution was slowly added dropwise to the solution. The color of the solution gradually changed from light yellow to reddish brown, then to dark green, and finally to dark blue. Keeping the temperature constant, the ultrasonic treatment was continued for 1 hour to allow the reaction to proceed fully. After the reaction was completed, the water was evaporated to obtain a dark blue wet gel. The wet gel was dried in a drying oven at 100°C for 2 hours to obtain a loose and porous dark blue LiV3O8 precursor material. The material coated with the LiV3O8 precursor was placed in a muffle furnace and calcined at 500°C for 20 hours to obtain coated material A.
[0158] (2) 0.1 mol of material A was added to an aqueous solution containing 2 mol of LiOH, 0.0125 mol of TiCl4 and 0.0042 mol of NiCl2, and the mixed solution was reacted in a hydrothermal reactor at 200°C for 24 h. After the hydrothermal reaction was completed, the mixture was filtered and the obtained solid was sintered at 300°C for 5 h to obtain material B.
[0159] (3) Add 0.1 mol of material B to a solution containing 0.005 mol of FeSO4·7H2O, 0.005 mol of H3PO4 and 0.015 mol of LiOH·H2O, adjust the pH value of the mixed solution with sodium carbonate, and add the surfactant polyvinyl alcohol when the pH value of the mixed solution is 8.5. Transfer the solution to a hydrothermal reactor, and set the reaction temperature to 150°C and the reaction time to 10 h. After the hydrothermal reaction is completed, filter the solution, and sinter the obtained solid at 250°C for 3 h to obtain the positive electrode active material.
[0160] Example 4
[0161] (1) Purchase 0.1 mol LiNi 0.8 Co 0.1 Mn 0.1O2 (Guangzhou Bangpu Technology) was ground and added to a beaker. 0.014 mol LiOH·H2O and 0.042 mol NH4VO3 were mixed and added to the beaker together and dissolved in a certain amount of deionized water. A saturated citric acid solution was prepared, in which the molar mass of citric acid was equal to the total number of moles of metal ions. The mixed salt solution was stirred with a magnetic stirrer at 80°C to make it uniformly dispersed in water. When the solution formed a uniform system, it was ultrasonically treated and the saturated citric acid solution was slowly added dropwise to the solution. The color of the solution gradually changed from light yellow to reddish brown, then to dark green, and finally to dark blue. Keeping the temperature constant, the ultrasonic treatment was continued for 1h to allow the reaction to proceed fully. After the reaction was completed, the water was evaporated to obtain a dark blue wet gel. The wet gel was dried in a drying oven at 100°C for 2h to obtain a loose and porous dark blue LiV3O8 precursor material. The material coated with the LiV3O8 precursor was placed in a muffle furnace and calcined at 500°C for 20 hours to obtain material A.
[0162] (2) 0.1 mol of material A was added to an aqueous solution containing 2 mol of LiOH, 0.015 mol of TiCl4, and 0.005 mol of NiCl2, and the mixed solution was reacted in a hydrothermal reactor at 200°C for 24 hours. After the hydrothermal reaction was completed, the mixture was filtered and the obtained solid was sintered at 300°C for 5 hours to obtain material B.
[0163] (3) Add 0.1 mol of material B to a solution containing 0.006 mol of FeSO4·7H2O, 0.006 mol of H3PO4 and 0.018 mol of LiOH·H2O, adjust the pH value of the mixed solution with sodium carbonate, and add the surfactant polyvinyl alcohol when the pH value of the mixed solution is 8.5. Move the solution to a hydrothermal reactor, and set the reaction temperature to 150°C and the reaction time to 10 h. After the hydrothermal reaction is completed, filter the solution, and sinter the obtained solid at 250°C for 3 h to obtain the positive electrode active material.
[0164] Example 5
[0165] (1) Purchase 0.1 mol LiNi 0.8 Co 0.1 Mn 0.1O2 (Guangzhou Bangpu Technology) was ground and added to a beaker. 0.0163 mol LiOH·H2O and 0.049 mol NH4VO3 were mixed and added to the beaker together and dissolved in a certain amount of deionized water. A saturated citric acid solution was prepared, in which the molar mass of citric acid was equal to the total number of moles of metal ions. The mixed salt solution was stirred with a magnetic stirrer at 80°C to make it uniformly dispersed in water. When the solution formed a uniform system, it was ultrasonically treated and the saturated citric acid solution was slowly added dropwise to the solution. The color of the solution gradually changed from light yellow to reddish brown, then to dark green, and finally to dark blue. Keeping the temperature constant, the ultrasonic treatment was continued for 1 hour to allow the reaction to proceed fully. After the reaction was completed, the water was evaporated to obtain a dark blue wet gel. The wet gel was dried in a drying oven at 100°C for 2 hours to obtain a loose and porous dark blue LiV3O8 precursor material. The material coated with the LiV3O8 precursor was placed in a muffle furnace and calcined at 500°C for 20 hours to obtain material A.
[0166] (2) 0.1 mol of material A was added to an aqueous solution containing 2 mol of LiOH, 0.0175 mol of TiCl4 and 0.006 mol of NiCl2, and the mixed solution was reacted in a hydrothermal reactor at 200°C for 24 hours. After the hydrothermal reaction was completed, the mixture was filtered and the obtained solid was sintered at 300°C for 5 hours to obtain the coated material B.
[0167] (3) Add 0.1 mol of material B to a solution containing 0.007 mol of FeSO4·7H2O, 0.007 mol of H3PO4 and 0.021 mol of LiOH·H2O, and adjust the pH value of the mixed solution with sodium carbonate. When the pH value of the mixed solution is 8.5, add the surfactant polyvinyl alcohol. Move the solution to a hydrothermal reactor, and set the reaction temperature to 150°C and the reaction time to 10 h. After the hydrothermal reaction is completed, filter the solution, and sinter the obtained solid at 250°C for 3 h to obtain the positive electrode active material.
[0168] Comparative Example 1
[0169] LiNi 0.8 Co 0.1 Mn 0.1 O2 (Guangzhou Brunp Technology)
[0170] In order to further illustrate the variation between samples, the sample information of the above examples and comparative examples is summarized in the following Table 1.
[0171] Table 1 Summary of sample information of examples and comparative examples
[0172]
[0173] The first layer, the second layer, and the third layer in Table 1 are in the order from the substrate surface to the outside, that is, from the substrate surface to the outside, they are the first layer, the second layer, and the third layer.
[0174] Preparation of lithium-ion secondary batteries
[0175] The positive electrode active materials of Examples 1-5 and Comparative Example 1 were respectively mixed with the conductive agent carbon black, the binder polyvinylidene fluoride (PVDF), and the solvent N-methylpyrrolidone (NMP) at a weight ratio of 67.34:30:28.86:2.7:1.1, and the positive electrode slurry was obtained after mixing evenly. The positive electrode slurry was evenly coated on the positive electrode collector, and the positive electrode sheet of the comparative example was obtained after drying, cold pressing, and slitting.
[0176] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare cell, the bare cell is welded with a pole ear, and the bare cell is placed in an aluminum shell, and baked at 100°C to remove water, and then the electrolyte is injected and sealed to obtain a battery. The battery is sequentially subjected to the processes of static, hot and cold pressing, formation, shaping, and capacity testing to obtain the lithium ion secondary battery products of Examples 1-5 and Comparative Example 1.
[0177] Battery performance test
[0178] 1. Battery DCR test
[0179] Test Method
[0180] The secondary battery was charged to 4.4V at 1 / 3C constant current, then charged to 0.05C at 4.4V constant voltage, then discharged to 50% SOC, left to stand for 5 minutes, recorded voltage V1, then discharged at 4C current for 10s, recorded voltage V2, (V2-V1) / I is DCR. (HPPC test power calculation formula is U / R*cutoff voltage=P).
[0181] 2. Battery capacity retention test
[0182] Test Method
[0183] At 25°C, the batteries corresponding to Examples 1-5 and Comparative Example 1 were charged to 4.4V at a constant current of 1 / 3C, then charged to a current of 0.05C at a constant voltage of 4.4V, left for 5 minutes, and then discharged to 2.0V at a constant current of 1 / 3C. The obtained capacity was recorded as the initial capacity C0. Repeat the above steps for the same battery, and record the discharge capacity Cn of the battery after the nth cycle at the same time. The battery capacity retention rate Pn after each cycle = Cn / C0*100%.
[0184] Experimental Results and Discussion
[0185] Table 2 Performance test table of Examples 1-5 and Comparative Example 1
[0186]
[0187] It can be seen from the calculation formula of the HPPC test power that the DCR of the battery is inversely proportional to the power, that is, the smaller the battery DCR, the greater the power. As can be seen from Table 2, in Examples 1-5 and Comparative Example 1, the DCR of Examples 1-5 is less than that of Comparative Example 1, that is, the battery power of Examples 1-5 is better than that of Comparative Example 1. At 30% SOC and 20% SOC, the power performance of Examples 1-3 is improved by 10% over that of Comparative Example 1; at 10% SOC, the power performance of Examples 1-3 is improved by 20% over that of Comparative Example 1, among which Example 2 has the best effect. The experimental results show that the positive electrode active material with a coating layer can reduce the DC resistance of the system and improve the power performance of the battery cell at low SOC. Among them, when the thickness of the three coating layers is 40nm, the secondary battery performance is optimal.
[0188] From the battery capacity retention results in Table 2, it can be seen that in Examples 1-5 and Comparative Example 1, when the capacity retention rate decays to 80%, the number of cycles of Examples 1-5 is greater than that of Comparative Example 1, among which the number of cycles of Example 2 is the largest. This experimental result shows that the positive electrode active material with a coating layer can improve the cycle performance of the battery.
[0189] In summary, the cathode active material disclosed in the present invention can improve the power performance of the battery at low SOC while also improving the cycle performance of the battery.
Claims
1. A positive electrode active material, comprising a matrix and a coating layer, wherein the matrix comprises Li 1+ a Ni x Co y Mn z M b N c O2, where M and N are one of Al, Fe, Zn, V, Cr, Nb, Ca and Mg respectively, and the values of a, b, c, x, y and z satisfy the following conditions at the same time: 0<a<0.2, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤b≤1, 0≤c≤1, and x+y+z+b+c=1; The coating layer has a three-layer structure, which includes a first coating layer, a second coating layer and a third coating layer in order from the surface of the substrate to the outside. The first coating layer is Li 1+x1 V3O8, the second coating layer is Li 1.2 Ti x2 Ni y2 O2, the third coating layer is LiMn x3 Fe y3 PO4, where 0≤x1≤0.2, 0≤x2≤0.8, 0≤y2≤0.8, x2+y2=0.8, 0≤x3≤1, 0≤y3≤1, x3+y3=1.
2. The positive electrode active material according to claim 1, wherein The first coating layer is LiV3O8, and the second coating layer is Li 1.2 Ti 0.6 Ni 0.2 O2, the third coating layer is LiMn 0.75 Fe 0.25 At least one of PO4 or LiFePO4.
3. The positive electrode active material according to claim 2, wherein The thickness of the first coating layer is 20-100 nm.
4. The positive electrode active material according to claim 2, wherein The thickness of the first coating layer is 30-70 nm.
5. The positive electrode active material according to claim 3, wherein The thickness of the second coating layer is 20-100 nm.
6. The positive electrode active material according to claim 3, wherein The thickness of the second coating layer is 30-70 nm.
7. The positive electrode active material according to claim 5, wherein The thickness of the third coating layer is 20-100 nm.
8. The positive electrode active material according to claim 5, wherein The thickness of the third coating layer is 30-70 nm.
9. A method for preparing the positive electrode active material according to any one of claims 1 to 8, the method comprising at least the following steps: Step (1): adding the matrix, lithium source and vanadium source into an aqueous solution in a molar ratio, adding a citric acid solution and drying, and then sintering to obtain material A; Step (2): adding the material A to an aqueous solution containing a lithium source, a nickel source and a titanium source for hydrothermal reaction, filtering after the hydrothermal reaction, and sintering the obtained solid to obtain material B; Step (3): adding the material B to an aqueous solution containing a lithium source, an iron source and a phosphorus source, adjusting the pH of the solution and adding a surfactant to carry out a hydrothermal reaction, filtering after the hydrothermal reaction is completed, and sintering the obtained solid to obtain the positive electrode active material.
10. The method according to claim 9, wherein: In the step (1), the sintering temperature is 300-800° C. and the sintering time is 12-24 hours.
11. The method according to claim 10, wherein: In the step (2), the hydrothermal reaction temperature is 150-250° C., and the hydrothermal reaction time is 12-48 hours.
12. The method according to claim 11, wherein: In the step (3), the hydrothermal reaction temperature is 100-200° C., and the hydrothermal reaction time is 6-24 h. 13 . A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises the positive electrode active material according to claim 1 . 14 . A battery module comprising the secondary battery according to claim 13 .
15. A battery pack, wherein the battery comprises the battery module according to claim 14. 16 . An electrical device, comprising at least one selected from the group consisting of the secondary battery of claim 13 , the battery module of claim 14 , and the battery pack of claim 15 .
Citation Information
Patent Citations
Multicomponent material with multilayer coating structure for lithium ion battery and preparation method thereof
CN101997113A
Modified lithium ion battery cathode material, preparation method thereof, and electrochemical energy saving apparatus using same
CN107516731A